High glucose restraint of acetylcholine-induced keratinocyte epithelial-mesenchymal transition is mitigated by p38 inhibition - Tan, Mark Wei Yi (2022)
Non-neuronal acetylcholine (Ach) plays important roles in various aspects of cell biology and homeostasis outside the neural system. Keratinocytes (KCs) have a functional cholinergic mechanism, suggesting that they respond to Ach. However, the physiological role and mechanism by which Ach modulates wound KC behavior in both nondiabetic and diabetic conditions are unexplored. We found an enrichment in neurotransmitter-related pathways in microdissected-migrating nondiabetic and diabetic KCs. We showed that Ach upregulated TGFβRII through Src-extracellular signal‒regulated kinase 1/2 pathway to potentiate TGFβ1-mediated epithelial‒mesenchymal transition in normoglycemic condition. Unexpectedly, KCs were nonresponsive to the elevated endogenous Ach in a hyperglycemic environment. We further showed that the activation of p38 MAPK in high glucose condition interferes with Src-extracellular signal‒regulated kinase 1/2 signaling, resulting in Ach resistance that could be rescued by inhibiting p38 MAPK. A better understanding of the cholinergic physiology in diabetic KCs could improve wound management and care. The finding suggests that mitigating the inhibitory effect of diabetic wound microenvironment has a direct clinical implication on the efficacy and safety of various wound healing agents to improve chronic diabetic wounds.